2014
DOI: 10.1016/j.toxlet.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic acid feeding results in direct hepato-toxicity independent of neutrophil function in mice

Abstract: Lithocholic acid (LCA) supplementation in the diet results in intrahepatic cholestasis and bile infarcts. Previously we showed that an innate immune response is critical for cholestatic liver injury in the bile duct ligated mice. Thus, the purpose of this study was to investigate the role of neutrophils in the mechanism of liver injury caused by feeding mice a diet containing LCA. C57BL/6 mice were given control or 1% LCA containing diet for 24–96h and then examined for parameters of hepatotoxicity. Plasma ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…In cholestasis induced by LCA, the liver injury is caused by an overload of bile acids (Woolbright et al 2014;Yu et al 2015). Super increase in ALT and severe necrosis in the liver tissues were reported when the ALP increased by twofold (Woolbright et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In cholestasis induced by LCA, the liver injury is caused by an overload of bile acids (Woolbright et al 2014;Yu et al 2015). Super increase in ALT and severe necrosis in the liver tissues were reported when the ALP increased by twofold (Woolbright et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids play an important role in the enterohepatic system, but the corresponding cytotoxicity to hepatocytes should also be addressed [1,2] . Numerous studies have suggested that the intrahepatic accumulation of bile acids may directly or indirectly cause further damage to the liver [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important aspect of these new data is the elucidation of vast differences in individual bile acid concentrations in rodents and humans, both in control patients and during cholestatic liver injury [1]. While numerous studies [6, 12, 13] have focused on administering micromolar levels of toxic bile acids or their conjugate salt, such as glycochenodeoxycholate (GCDC) or taurolithocholate (TLC), to hepatocytes in vitro, newer data based on mass spectrometric bile acid analysis questions the use of micromolar concentrations of these bile acids in rodent cultures, as they likely do not accumulate to similar values in any compartment in vivo [8, 10]. Moreover, murine hepatocytes are highly resistant to TLC-induced injury in vitro, suggesting mechanisms of toxicity specific to the rat [10, 14].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies [6, 12, 13] have focused on administering micromolar levels of toxic bile acids or their conjugate salt, such as glycochenodeoxycholate (GCDC) or taurolithocholate (TLC), to hepatocytes in vitro, newer data based on mass spectrometric bile acid analysis questions the use of micromolar concentrations of these bile acids in rodent cultures, as they likely do not accumulate to similar values in any compartment in vivo [8, 10]. Moreover, murine hepatocytes are highly resistant to TLC-induced injury in vitro, suggesting mechanisms of toxicity specific to the rat [10, 14]. Additionally, the use of unconjugated bile acids to investigate pathophysiology seems unwarranted as more than 99 % of bile acids in liver, plasma and bile are conjugated to taurine or glycine in multiple species [79, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation